2022
DOI: 10.1183/23120541.00579-2021
|View full text |Cite
|
Sign up to set email alerts
|

An externally validated fully automated deep learning algorithm to classify COVID-19 and other pneumonias on chest computed tomography

Abstract: PurposeIn this study, we propose an Artificial Intelligence framework based on 3D Convolutional Neural network (CNN) to classify CT scans of patients with COVID-19, Influenza/CAP, and no-infection, after automatic segmentation of the lungs and lung abnormalities.MethodsThe AI classification model is based on inflated 3D Inception architecture and was trained and validated on retrospective data of CT images of 667 adult patients (No infection: 188, COVID-19: 230, Influenza/CAP: 249) and 210 adult patients (No i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Clearly, the proposed ACSN model showed superior performance compared to other methods in all indicators compared with the results published by Covid-Fact [ 40 ] and Vaidyanathan [ 41 ]. Moreover, compared with the results of Mohamed et al’s study [ 43 ], the ACSN model was not superior in all indicators but did surpass it in some regards, especially in terms of specificity, with 1.4% better results.…”
Section: Experiments and Analysissupporting
confidence: 55%
“…Clearly, the proposed ACSN model showed superior performance compared to other methods in all indicators compared with the results published by Covid-Fact [ 40 ] and Vaidyanathan [ 41 ]. Moreover, compared with the results of Mohamed et al’s study [ 43 ], the ACSN model was not superior in all indicators but did surpass it in some regards, especially in terms of specificity, with 1.4% better results.…”
Section: Experiments and Analysissupporting
confidence: 55%
“…For instance, machine learning algorithms can be used to analyze images obtained through X-ray and/or visible light imaging, thereby enabling the automatic classification of limb injuries cases by the trained model. In the literature, numerous studies have investigated the use of machine learning in interpreting CT scans for human diagnostics ( Lassau et al, 2021 ; Vaidyanathan et al, 2022 ). For example, predicting the severity of COVID-19 patients based on chest CT scans is one such application.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Algorithms and artificial intelligence models created using COVID-19 thoracic CT imaging data provide valuable insights into the diagnosis and prognosis of the disease. [23,24] The COVID-19 Reporting and Data System were established in 2020 with the aim of standardizing COVID-19 CT findings. [25] Microthrombi and the coagulation cascade are important in the pathophysiology of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…FARI has been presented as a marker of thrombosis risk, inflammation, and nutritional status. [23] In the present study, we compared OR-PNI with FARI and PNI, as they are considered predictors of mortality in intense inflammatory processes such as COVID-19. The results showed that the FARI value is effective in predicting mortality rather than PNI and OR-PNI.…”
Section: Discussionmentioning
confidence: 99%